Employee Empowerment in the Banking Sector - M.V, Dr. Archana; Tuteja, Dr. Sumedha; MS, Smt.Shilpashree; Khandwe, Prof. Aditya; Gupta, Dr. Sushil Kumar; Sharma, Vikas Rajkumar (The journal of contemporary issues in business and government, 2021)
Employee empowerment is one such tool for building trustful relationship in the work place which also initiates high level performance. In an organization if employees suffer from role ambiguity or role conflicts this can adversely influence the organizational performance and also hinder individual performance resulting in loss of interest among the employees. In order to overcome this, every organization has to implement empowerment techniques which enhance the confidence of the employees and also the interest of employees in their role and contribution. Employee empowerment has always flaunted positive impact on the mindset of the employees which in turn helps in improving their working ability as well as overall performance of the organization. It provides freedom to the employee to share their innovative ideas to improve the organization in the long run.